Amino acid substitutions in the poliovirus maturation cleavage site affect assembly and result in accumulation of provirions. - Ansardi, D C (1995)
The assembly of infectious poliovirus virions requires a proteolytic cleavage between an asparagine-serine amino acid pair (the maturation cleavage site) in VP0 after encapsidation of the genomic RNA. In this study, we have investigated the effects that mutations in the maturation cleavage site have on P1 polyprotein processing, assembly of subviral intermediates, and encapsidation of the viral genomic RNA. We have made mutations in the maturation cleavage site which change the asparagine-serine amino acid pair to either glutamine-glycine or threonine-serine. The mutations were created by site-directed mutagenesis of P1 cDNAs which were recombined into wild-type vaccinia virus to generate recombinant vaccinia viruses. The P1 polyproteins expressed from the recombinant vaccinia viruses were analyzed for proteolytic processing and assembly defects in cells coinfected with a recombinant vaccinia virus (VV-P3) that expresses the poliovirus 3CD protease. A trans complementation system using a defective poliovirus genome was utilized to assess the capacity of the mutant P1 proteins to encapsidate genomic RNA (D. C. Ansardi, D. C. Porter, and C. D. Morrow, J. Virol. 67:3684-3690, 1993). The mutant P1 proteins containing the glutamine-glycine amino acid pair (VP4-QG) and the threonine-serine pair (VP4-TS) were processed by 3CD provided in trans from VV-P3. The processed capsid proteins VP0, VP3, and VP1 derived from the mutant precursor VP4-QG were unstable and failed to assemble into subviral structures in cells coinfected with VV-P3. However, the capsid proteins derived from VP4-QG did assemble into empty-capsid-like structures in the presence of the defective poliovirus genome. In contrast, the capsid proteins derived from processing of the VP4-TS mutant assembled into subviral intermediates both in the presence and in the absence of the defective genome RNA. By a sedimentation analysis, we determined that the capsid proteins derived from the VP4-TS precursor encapsidated the defective genome RNA. However, the cleavage of VP0 to VP4 and VP2 was delayed, resulting in the accumulation of provirions. The maturation cleavage of the VP0 protein containing the VP4-TS mutation was accelerated by incubation of the provirions at 37 degrees C. The results of these studies demonstrate that mutations in the maturation cleavage site have profound effects on the subsequent capability of the capsid proteins to assemble and provide evidence for the existence of the provirion as an assembly intermediate.